An Ability of Translating Covid-19 Related Article of English Department Student on Teaching and Education Faculty - Feby Meuthia Yusuf; Amalya Widya Sari (Fakultas Sastra Universitas Ekasakti, 2022)
This research is motiyated by the difficulties of students in translating article related COVID-19 from English into Bahasa Indonesia. The purpose of this study was determine by the ability of students in translating article. The method used in this research was descriptive gualitative method. In this research, the member of the population member was 14 students, the population was the students from English department 15